Normative Market Europe: the EU as a force for good in international sports governance?. Issue 1 (2nd January 2017) - Geeraert, Arnout; Drieskens, Edith
Abstract: Focusing on legal and policy externalisation, this article demonstrates the necessity of an integrated perspective for understanding the EU's unique identity in the governance of international sport. It shows that externalisation is characterised by a sequential stage process in which Normative Power Europe (NPE) and Market Power Europe (MPE) dynamics alternate and intertwine, bringing to life a Normative Market Europe . The EU's NPE identity forms the basis for a unique operating mode, aimed at strengthening the ethical character of international sports governance. The EU's potential to influence sport governing bodies like FIFA, however, emanates from its MPE identity, notably its large, regulated market. Yet interest contestation and lack of internal cohesiveness have often impeded the EU from becoming a force for good.